Tickle fetishism: pleasure beyond playfulness - Dagher, Sarah; Ishiyama, Shimpei (Frontiers in Psychology, 2024)
Tickling is commonly perceived as juvenile play associated with laughter. However, its potential connection to adult sexual behavior has largely remained unexplored. Our online survey, primarily distributed among individuals interested in tickle fetishism, explored tickling and its association with sexual behavior. Ticklishness types, tools, preferred body parts, and partner preferences, were examined. Results revealed diverse patterns of ticklishness changes over time and distinct body-part preferences for different types of tickling. Childhood experiences and exposure to tickling content in television were found to shape individuals’ affinity for tickle fetishism. A quarter of respondents reported experiencing orgasms exclusively from tickling, while around 88% expressed sexual satisfaction through tickling alone, indicating its sufficiency as a sexual stimulus among fetishists. Tickling desire decreased after orgasm, indicating an association between tickling and sexual activity. Moreover, ticklishness degree predicted preferences for being tickled rather than tickling others. Exploratory factor analysis identified three factors underlying tickling and sexual experiences: enjoyment and frequency of tickling during sexual activity; preference for intense sexual experiences; age of becoming sexually active. In conclusion, this study provides unique insights into tickling and its connections to sexual context, enhancing our understanding of diverse human sexual behavior and tickle fetishism as a distinct preference.